Tact maxims in asking questions in English teaching learning process - Napitupulu, Fenty Debora; Sianturi, Sri Sofian; Sipayung, Kammer; Tampubolon, Sahlan (Linguistics and Culture Review, 2021)
Objectives: This paper aims to describe the forms of tact maxims of asking questions in the English teaching-learning process. Methods: This paper applied qualitative research, where the data collection was observation. Result: There are twenty-four forms of tact maxims of asking questions in the English teaching-learning process. Conclusion: the tact maxim with politeness rules is in the polite category. Speakers ask questions using question words without threatening the face of the hearer.